2019
DOI: 10.1016/j.ijmedinf.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpreting the nursing record for an electronic context

Abstract: Background: This article seeks to facilitate the re-imagining of nursing records purposefully within an electronic context. It questions existing approaches to nursing documentation, critically examines existing nursing record systems and identifies new requirements. Methods: A comprehensive literature review was conducted to identify themes, that might meaningfully contribute to a new approach to nursing record systems development, around four key interrelated areas-standards, decision making, abstraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 55 publications
0
29
0
4
Order By: Relevance
“…This allows the right information on when, where, how and to whom it is needed to be provided 24/7 and improves decision‐making, resulting in significantly better health and financial outcomes (Harrington 2019). EHRs can evolve into clinical decision support systems, giving health professionals information and guidance when a decision needs to be taken (Hardiker et al 2019). An umbrella review conducted to reveal quality criteria, instruments and requisites for nursing documentation concluded that nurse documentation must align with the nursing process and use standard terminologies, user‐friendly formats and systems, to achieve high quality (De Groot et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows the right information on when, where, how and to whom it is needed to be provided 24/7 and improves decision‐making, resulting in significantly better health and financial outcomes (Harrington 2019). EHRs can evolve into clinical decision support systems, giving health professionals information and guidance when a decision needs to be taken (Hardiker et al 2019). An umbrella review conducted to reveal quality criteria, instruments and requisites for nursing documentation concluded that nurse documentation must align with the nursing process and use standard terminologies, user‐friendly formats and systems, to achieve high quality (De Groot et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It contains a set of predefined and agreed‐upon terms structured by nurses (Tastan et al 2014). Deciding upon which standards to use in EHR brings consistency to the process and accuracy, efficiency, reliability and comparability of health information at local, regional, national and international levels (Hardiker et al 2019). To deliver excellent care quality and reduce healthcare costs across health systems in different countries, it is relevant that diverse computer systems share content and its meaning accurately and reliably – semantic interoperability (Gavrilov et al 2019; Harrington 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A baixa qualidade nos registros de enfermagem pode ocasionar problemas graves, que repercutem diretamente na qualidade da assistência e na segurança do paciente, e envolve tanto os profissionais da prática assistencial quanto os gestores, órgãos de classe, pesquisadores e docentes 18 . A adoção de normas e rotinas específicas para as anotações de enfermagem permite padronizar a práticas dos registros, refletindo diretamente na qualidade da assistência, segurança e comunicação 19,20 .…”
Section: O Registro Garante a Segurança Do Paciente Onde Tudo Deve Estar Ali Registrado Corretamente O Que Foi Feito Com Ele De Forma Claunclassified
“…33 However, significant shortcomings have been reported in the functions of information systems in terms of how well they support nurses' work and nursing documentation. [34][35][36] Overall, little is known about the role of information system's documentation support and nurses' documentation competence in the detection of documentation-related errors that cause adverse events. However, according to above-mentioned previous research, it can be assumed that if the information system poorly supports nursing documentation, it may also increase the risk of documentation-related errors.…”
Section: Introductionmentioning
confidence: 99%